Thrombocytopenia in bacteraemia and association with bacterial species. Issue 10 (15th May 2018) - Johansson, D.; Rasmussen, M.; Inghammar, M.
Abstract: Thrombocytopenia is common in patients with invasive bacterial infections. Bacteria can activate platelets, but it is unclear if this affects platelet count. The aim of this study was to examine whether bacteraemia with Staphylococcus aureus, which readily activate human platelets, was more likely to be complicated by thrombocytopenia than bacteraemia with Escherichia coli or Streptococcus pneumoniae with different abilities to activate platelets. We compared information from 600 adult patients with community-acquired bacteraemia with S. aureus ( n = 140), E. coli ( n = 420) and S. pneumoniae ( n = 40) in Southern Sweden, 2012, linking information on positive blood cultures from microbiological databases and medical charts. The proportion of patients with thrombocytopenia (platelet count <150 × 10 9 /ml) was calculated. Logistic regression was used to estimate the odds ratios (OR) for thrombocytopenia according to bacterial species adjusted for confounders. The proportion of thrombocytopenia was 29% in S. aureus, 28% in E. coli and 20% in S. pneumonia bacteraemia ( P = 0.50), corresponding to an OR of 1.2 (95% confidence interval 0.7–1.9) for thrombocytopenia for S. aureus as compared with E. coli or S. pneumoniae, adjusted for confounders. This study indicates that platelet activation by bacteria is not a major causative mechanism in sepsis-associated thrombocytopenia.